2017
DOI: 10.3389/fnmol.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Alpha-Secretase ADAM10 In vitro and In vivo: Genetic, Epigenetic, and Protein-Based Mechanisms

Abstract: ADAM10 (A Disintegrin and Metalloproteinase 10) has been identified as the major physiological alpha-secretase in neurons, responsible for cleaving APP in a non-amyloidogenic manner. This cleavage results in the production of a neuroprotective APP-derived fragment, APPs-alpha, and an attenuated production of neurotoxic A-beta peptides. An increase in ADAM10 activity shifts the balance of APP processing toward APPs-alpha and protects the brain from amyloid deposition and disease. Thus, increasing ADAM10 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 200 publications
(262 reference statements)
0
64
1
Order By: Relevance
“…Thus, increased activity of ADAM10 has been proven to be an effective way in treating neurodegenerative diseases and inhibiting β‐amyloid deposition in brain. [ 14 ] The results in this study indicated that AR‐C17 could significantly improve ADAM10 protein expression and reduce β‐amyloid deposition. It is a well‐documented notion that synaptic failure induced by Aβ toxicity, tau hyperphosphorylation, and mitochondrial dysfunction are closely associated with cognitive deficits.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, increased activity of ADAM10 has been proven to be an effective way in treating neurodegenerative diseases and inhibiting β‐amyloid deposition in brain. [ 14 ] The results in this study indicated that AR‐C17 could significantly improve ADAM10 protein expression and reduce β‐amyloid deposition. It is a well‐documented notion that synaptic failure induced by Aβ toxicity, tau hyperphosphorylation, and mitochondrial dysfunction are closely associated with cognitive deficits.…”
Section: Discussionmentioning
confidence: 85%
“…NMDAR are nonselective cations channels, highly permeable to calcium ions. Given the fact that ADAM10 is ubiquitously expressed in the central nervous system of adult mice [38,39] and calcium influx is known activator of ADAM10, NMDAR agonist-stimulated increase in calcium concentration may result in enhanced ADAM10 activity, leading to rapid NRG2 shedding. However, the results presented by Vullhorst and Buonanno [37] may suggest that ADAM10 is not the only protease responsible for NRG2 shedding, because inhibition of ADAM10 (and metalloproteases in general) had less profound effect on NRG2 shedding than NMDAR antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…Target genes for the Notch pathway assay were selected according to the same principles as described before, using available scientific literature 22,24 . The probesets of direct target genes from publicly available Affymetrix (Santa Clara, USA) HG-U133Plus2.0 microarray datasets were selected using the Bioconductor package hgu133plus2.db available in the statistical environment R and manually curated using GRCh38/hg38 available on the UCSC Genome Browser (www.genome.ucsc.edu, last access 2-17-2020) 26,28,32,40,41 . Probesets representing intronic sequences, probesets on opposite strands or other chromosomal sequences than the respective target gene were excluded.…”
Section: Development Of the Notch Pathway Assaymentioning
confidence: 99%